Efektivitas ekstrak biji ketumbar (Corriandrum sativum L.) terhadap Gambaran histopatologik sel busa aterosklerosis aorta abdominalis tikus model hiperkolesterolemia diabetes - Kusvandita Giopratiwi, (2020)
Coriander Seed Extract (CSE) is thought to have the potential to repair foam cell formation process which is part of atherosclerotic lesion. The aim of this study is to identify the effects of coriander seed extract on histopathological features of atherosclerotic foam cells abdominal aorta in rats hypercholesterolemia diabetes model. The study was conducted for 63 days. 30 rats were grouped into five groups, each group consist of 6 rats. Negative control group (standar feed), positive control group (high fat diet and alloxan + glibenclamide 0.045 mg), treatment group 1 (high fat diet and alloxan + CSE 300 mg/kgBB/day), treatment group 2 (high fat diet and alloxan + CSE 500 mg/kgBB/day), treatment group 3 (high fat diet and alloxan + CSE 700 mg/kgBB/day). After the treatment were given to each group, the next procedure were dissection, extraction of the aorta abdominal organ, and histopathological examination of foam cell. Data were analyzed with One Way ANOVA test and Post Hoc Bonferoni test show there are significant difference (P value = 0.049) between positive control group and treatment group 3. In conclusion, CSE 700 mg/kgBB dose can reduce foam cell formation.